2019
DOI: 10.1093/gji/ggz272
|View full text |Cite
|
Sign up to set email alerts
|

Along-strike variation in slab geometry at the southern Mariana subduction zone revealed by seismicity through ocean bottom seismic experiments

Abstract: SUMMARYWe have conducted the first passive Ocean Bottom Seismograph (OBS) experiment near the Challenger Deep at the southernmost Mariana subduction zone by deploying and recovering an array of 6 broad-band OBSs during December 2016–June 2017. The obtained passive-source seismic records provide the first-ever near-field seismic observations in the southernmost Mariana subduction zone. We first correct clock errors of the OBS recordings based on both teleseismic waveforms and ambient noise cross-correlation. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 64 publications
1
28
0
Order By: Relevance
“…Most seismicity beneath the outer forearc is found in the north, where the forearc is less wide, and OBS stations were closer to the trench. We note that more smaller earthquakes may be found using template-matching techniques (e.g., Zhu et al, 2019). Here, we focussed on the larger events with robust arrival time determination, particularly for the generation of a well-constrained 1-D seismic velocity, with less emphasis on the evolution of seismicity in time and space.…”
Section: Overall Characteristics Of La Seismicity and Subduction Geommentioning
confidence: 99%
“…Most seismicity beneath the outer forearc is found in the north, where the forearc is less wide, and OBS stations were closer to the trench. We note that more smaller earthquakes may be found using template-matching techniques (e.g., Zhu et al, 2019). Here, we focussed on the larger events with robust arrival time determination, particularly for the generation of a well-constrained 1-D seismic velocity, with less emphasis on the evolution of seismicity in time and space.…”
Section: Overall Characteristics Of La Seismicity and Subduction Geommentioning
confidence: 99%
“…2), the Malaguana-Gadao Ridge south of 13°05′N, the diffuse spreading zone, and the Southwest Mariana Rift overlie the Pacific slab at depths of 100 km or less. A local ocean-bottom seismometer study centered over the Southwest Mariana Rift and the forearc found somewhat deeper slab depths in some areas >~80 km from the trench, but also confirmed the presence of the slab beneath the Malaguana-Gadao Ridge and diffuse spreading zone (Zhu et al, 2019). In this setting, abundant slab dewatering is predicted by studies of the metamorphic breakdown of hydrous Research Paper minerals (Peacock, 1990;Schmidt and Poli, 1998), leading to enhanced melt production.…”
Section: Volcanism In the Southern Mariana Regionmentioning
confidence: 71%
“…In this part of the basin, the trench curves to the west and becomes increasingly oriented in the direction of trough opening (Fryer et al, 1998;Kato et al, 2003), creating a strong component of trench-parallel extension within the Mariana platelet forearc (Martinez et al, 2000(Martinez et al, , 2018 that is separate from the trench-normal extension in the backarc basin. The divergent boundary in the backarc curves westward in concert with the trench, and its morphology changes from the magmatically robust seafloor spreading center of the Malaguana-Gadao Ridge (Martinez et al, 2000;Becker et al, 2010) in the northeastern part of our study area to a predominantly tectonic rift at the narrow (~40 km) Southwest Mariana Rift (Becker, 2005;Wan et al, 2019) in the west (Figs. 2 and 3).…”
Section: ■ Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Statistical analyses of trenches in the western Pacific (Lallemand et al, 2005) and near-field seismic observations (Zhu et al, 2019) show an average slab dip of 28°at shallow depth (Figure 3b), so we initiate the subduction by prescribing a 28°dipping weak fracture zone between the continental and oceanic plates. This weak zone consists of mantle rocks with wet olivine rheology (Chopra & Paterson, 1981;Ranalli, 1995) Figure 2.…”
Section: Numerical Model Descriptionmentioning
confidence: 87%